Towards a new diocese with Pope Francis - Osorio Torres, Juan Alberto (2014)
The importance of the diocese as a social unit for the project about structural reform of the Church is highlighted; which the Pope Francis has set in his first letter, “The joy of the Gospel”. This project means a real foundation of the diocese, because it demands the return of the Church to the Gospel, and reminds it its condition as primary subject of this structural reform. From an anthropological approach of the diocese, the early contribution to this process of the Archdiocese of Lima from 1954 to 1996 is spelled out. Due to this experience, the diocese ceased to function as a symbolic powerstructure from top to bottom, because the migratory waves and provincial protagonists succeeded in transforming from below and from within the exercise of that power, turning and reversing its conventional orientation.